Problematika Pemutusan Hubungan Kerja (PHK) Berdasarkan Perjanjian Kerja Waktu Tidak Tertentu (PKWTT) Secara Lisan - Rahman, Abdur (Wajah Hukum, 2024)
An employment relationship occurs because of a working agreement, either a work agreement for a certain time or a work agreement for an indefinite time. An agreement is valid if it has elements of agreement between both parties; ability or competence to carry out legal actions; there is an object agreed upon and does not conflict with applicable laws and regulations. Employment agreements can be made in writing and verbally. PKWT must be made in writing while PKWTT can be made in writing or verbally. What are the legal consequences if a PKWTT is carried out in verball agreement? What are the legal consequences if an entrepreneur lays off a PKWTT with an verball agreement? The research method used in this paper is normative juridical based on library materials and secondary data. The results of this paper ultimately provide the conclusion that the legal consequences of PKWTT with a verball agreement are the same as PKWTT with a written agreement, including in terms of termination of employment relations.